Trends in the use of timber in the built fabric of Copenhagen - Īle, Una; Stokmane, Ilze (Landscape Architecture and Art, 2024)
Innovative approach and existing natural values, proximity to water, green structure are key elements and aspects that combine sustainable activities with high quality of life in Copenhagen’s architecture and urban development as a whole. Whether it is new housing developments, new cycle routes, city parks, Copenhagen is at the forefront of architecture and is constantly, continuously preparing for a more sustainable future, while meeting the needs and aspirations of the local population. The most advanced and innovative knowledge from around the world has helped to make Copenhagen a sustainable city of the future, working with quality solutions in architecture, transport infrastructure, energy. At the same time, thinking about meeting the needs of the citizens, culminating in appropriate urban solutions, creating a quality urban fabric. The aim of the study is therefore to look at the trends in the use of timber in the built fabric of Copenhagen from the point of view of visual and aesthetic quality. The study describes the sites surveyed by the authors, based on previous experience and practice, and evaluates a modern building structure developed and designed in the 21st century.